2001
DOI: 10.1152/ajpregu.2001.280.3.r766
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of HBO on cerebral infarction in MCAO rats

Abstract: Various reports in the literature have shown that hyperbaric oxygen (HBO) reduces cerebral infarction both in animals and humans. After the initial ischemic insult, however, initiating HBO treatment at different intervals has yielded conflicting results. The present study was undertaken to determine the optimal therapeutic window in which to start HBO treatment for cerebral infarction after transient focal ischemia. In this study, the operator occluded the middle cerebral artery (MCA) of anesthetized rats by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 17 publications
10
57
0
5
Order By: Relevance
“…Animal experiments and clinical trials have shown that HBO performed within 6 h after HIBD may achieve favorable outcomes and promote the long-term neurological recovery (3)(4)(5)(6). In addition, numerous studies in China have demonstrated that HBO can reduce the disability and mortality of HIBD (7).…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments and clinical trials have shown that HBO performed within 6 h after HIBD may achieve favorable outcomes and promote the long-term neurological recovery (3)(4)(5)(6). In addition, numerous studies in China have demonstrated that HBO can reduce the disability and mortality of HIBD (7).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of a rat model of 2-hour MCA occlusion with HBO within 6 hours of reperfusion was found to decrease the area of infarction. 5) We believe that early application of HBO while the ischemic penumbra was viable was crucial to our favorable results.…”
Section: Discussionmentioning
confidence: 89%
“…Hyperbaric oxygen (HBO) therapy for acute cerebral ischemia has been evaluated by animal experiments 5,12,18,24) and human clinical observations. 3,8,10,13,15,20) The experimental studies suggested considerable potential, 5,12,18,24) but the clinical effectiveness in patients with acute ischemic stroke has been controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither a single treatment nor three treatments prevented the development of DNS. It is possible that HBO administered once the cascade of events leading to delayed neurologic damage was initiated resulted in additional oxidative stress and damage [23,24].…”
Section: Discussionmentioning
confidence: 99%